Alterations in AdeS and AdeR regulatory proteins in 1-(1-naphthylmethyl)-piperazine responsive colistin resistance of Acinetobacter baumannii - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2020)
Colistin resistant Acinetobacter baumannii strains are of great concern worldwide. However, the role of efflux pumps in colistin resistance needs to be elucidated. We investigated the changes in colistin MICs of 29 colistin resistant A. baumannii isolates in response to resistance-nodulation-division (RND)-type efflux pump inhibitor (EPI) and the alterations in AdeR and AdeS two-component regulatory proteins previously associated with the overproduction of AdeAB. The EPI, 1-(1-naphthylmethyl)-piperazine (NMP), led to significant reductions in colistin MICs. At least one of the following amino acid substitutions was found in AdeS proteins from 18 of the isolates: L172P, A94V, V27I, V32I, G186V, and G164A. Besides, A136V and V120I alterations were identified in AdeR from five isolates. Therefore, EPI-responsive colistin resistance in our isolates is most likely due to the action of an RND-type efflux system. The underlying mechanism of resistance might be the result of certain AdeRS alterations, leading to AdeAB overexpression.
Keywords: Acinetobacter baumannii; colistin; multidrug resistance; RND-type efflux pump; CCCP; NMP; gene overexpression; EFFLUX PUMP; MULTIDRUG-RESISTANCE; ADEABC; OVEREXPRESSION; TIGECYCLINE; EXPRESSION; SUSCEPTIBILITY; INFECTIONS; MECHANISMS; INHIBITORS